Nutritional Variation of Different Feed Ingredients and Compound Feed Found in Different Parts of Nepal - Tiwari, MR; Khanal, SK; Shrestha, B; Jha, RK (Nepal Agriculture Research Journal, 2009)
Many feed industries in various parts of the country have been producing and marketing different types of compound feeds. The source of feed ingredients also varies greatly which will ultimately lead to the variation in the quality of finished products. Altogether 493 samples of 50 different feed ingredients and compound feed were collected from Baglung, Baitadi, Banke, Chitwan, Darchula, Dolakha, Dolpa, Gorkha, Ilam, Jhapa, Kathmandu, Kaski, Lalitpur, Lamjung, Morang, Mahottary, Makwanpur, Myagdi, Nawal Parasi, Parbat, Parsa, Rasuwa, Rupandehi, Sankhuwasava, Sunsari, Saptari, Sarlahi, Sindhupalchok, Siraha, Syangja and Tanahun districts. Highest content of dry matter (99.51%), organic matter (98.45%), total ash (98.14%) and crude protein (67.85%) was recorded for oyster cell, white maize grain, oyster cell and meat meal respectively. Similarly, the rice husk was found to be superior in crude fibre content (34.46%) In terms of mineral oyster cell was found to be superior in calcium content (35.94%) and bone meal in phosphorous content (1.59%) as compared to other feed ingredients. Key words: Crude fibre; crude protein; dry matter; feed ingredients; organic matter; total ash DOI: 10.3126/narj.v7i0.1872 Nepal Agriculture Research Journal Vol.7 2006 pp.75-81